Current practice, problems and factors in COSD application a component users perspective - Aris H.; Salleh F.H.M.; Ibrahim Z.; Salim S.S. (2023)
Motivated by the absence of information on the status of component-oriented software development (COSD) application in Malaysia, a study was carried out to investigate the current state of COSD application amongst the software developers. The required information was obtained from the questionnaires distributed to the software developers working at various software development companies in Malaysia. The software developers are broadly categorised into component users and non-component users, where the former use components in their software development and the latter do not. In this paper, information on the component users' practice and the problems that they face in applying COSD is presented. Factors affecting the application of COSD are also included. Information on the current practice shows that the prospect of component users to continue using COSD is high and the room for improvement is wide. Therefore, a list of possible research areas were identified from the problems and factors gathered. The list of research areas, which is arranged in the order of influence, can serve as a basis for researchers to determine a COSD research area to be pursued. 2009 IEEE.